2021
DOI: 10.1159/000514759
|View full text |Cite
|
Sign up to set email alerts
|

Non-Muscle Invasive Bladder Cancer with Variant Histology: Biological Features and Clinical Implications

Abstract: Background: The most common bladder cancer (BC) histotype is pure urothelial carcinoma (UC), which may undergo divergent differentiation in some cases. Variant histology (VH) presents along variable morphologies, either single or combined between them or with pure UC. From a clinical standpoint, the vast majority of BC is diagnosed at non-invasive or minimally invasive stages, namely as non-muscle invasive BC (NMIBC). There is a wide range of therapeutic options for patients with NMIBC, according to their clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 143 publications
0
15
0
Order By: Relevance
“…Recently, many studies found varieties of diagnostic and prognostic biomarkers for cancer (32)(33)(34), few of which were utilized in clinical administration. A good biomarker can help identify cancers in the early stage, risk stratification, prognosis improvement, outcome prediction, variant histology (35), and targeted therapy (36). In this context, it is important to identify biomarkers that enable accurate prediction of recurrence, progression, and clinical outcome in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies found varieties of diagnostic and prognostic biomarkers for cancer (32)(33)(34), few of which were utilized in clinical administration. A good biomarker can help identify cancers in the early stage, risk stratification, prognosis improvement, outcome prediction, variant histology (35), and targeted therapy (36). In this context, it is important to identify biomarkers that enable accurate prediction of recurrence, progression, and clinical outcome in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As regards to genito-urinary tumors, clones SP263, SP142, 28-8, and 22C3 have been approved as assays to identify urothelial carcinoma patients that are most likely to benefit from various immunomodulants. To select eligible patients, each clone should be evaluated on the basis of specific score system and/or cut-off criteria (SSCC), according to current guidelines based on the results from large clinical trials: Atezolizumab (SP142; SSCC: ≥5% of positive immune cells); avelumab, durvalumab, and tislelizumab (SP263; SSCC: ≥25% of positive tumor or immune cells); nivolumab (28-8; SSCC: ≥1% of positive tumor cells); and pembrolizumab (22C3; CPS score) [167,168]. Such discrepancies in the recommended algorithms of evaluation reveal defective harmonization of PD-L1 immunohistochemical testing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while univariate and multivariate Cox regression analysis indicated that the m6A score may be an independent prognostic factor, a study has suggested distinguishing between invasive and non-invasive micropapillary carcinoma of the bladder, as the latter may not predict a poor prognosis ( 30 ). Variant histology may be related to survival outcomes ( 31 ). Further studies on the relationship between variant histology and m6A are still needed.…”
Section: Discussionmentioning
confidence: 99%